Investigation of the Phytochemicals Present in the Local Datura stramonium Seeds by Using Two Extraction Methods: Ala’a H. Merza, Khalil Z. Al- Jeboori, Nahi Y. Yaseen - Merza, Ala’a H. (The Iraqi Journal of Veterinary Medicine, 2010)
In order to investigate the phytochemicals presence in the seeds of local plant of Datura stramonium rather than alkaloids. For this purpose two types of Datura stramonium extract were prepared. The first was precipitated by acetone and the other was destructed by ether then precipitated with ammonium sulphate. The first extract yielded 2.5gram/ 5 gram of seeds weight; while, the second extract yielded 1.23 gram/ 5 gram of seed weight. Biochemical tests exhibited that lectin and trace amounts of glycosides were presented in the acetone precipitated extract. Whereas, the ether extract contained lectin, tannin, flavonoids, and trace amounts of alkaloids